2020
DOI: 10.31234/osf.io/eywhg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond Moral Dilemmas: The Role of Reasoning in Five Categories of Utilitarian Judgment

Abstract: Over the past two decades, the study of moral reasoning has been heavily influenced by Joshua Greene’s dual-process model of moral judgment, according to which deontological judgments are typically supported by intuitive, automatic processes while utilitarian judgments are typically supported by reflective, conscious processes. However, most of the evidence gathered in support of this model comes from the study of people’s judgments about sacrificial dilemmas, such as Trolley Problems. To which extent does thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Relationships between Cognitive style, Trust in Raoult and other beliefs. We found a positive correlation between intuitive cognitive style and belief in conspiracy theories, betimes (Jaquet & Cova, 2020). However, later analyses in this other study revealed that taking longer to fill the questionnaire did not lead participants to perform better on the Belief Bias task.…”
Section: H1: Connection Between Cognitive Styles and Trust In Raoultcontrasting
confidence: 45%
“…Relationships between Cognitive style, Trust in Raoult and other beliefs. We found a positive correlation between intuitive cognitive style and belief in conspiracy theories, betimes (Jaquet & Cova, 2020). However, later analyses in this other study revealed that taking longer to fill the questionnaire did not lead participants to perform better on the Belief Bias task.…”
Section: H1: Connection Between Cognitive Styles and Trust In Raoultcontrasting
confidence: 45%
“…Methodological style influences the content of a normative framework. Depending on which model of ethical reasoning you adopt, your commitment to impartiality can change significantly (Jaquet and Cova 2021). Foundational theorizing tends to press the demand for the impartial standpoint most firmly against everyday ethical beliefs, downplaying the significance of the personal in moral thought (Williams 2006), whereas intuitional theorizing limits what we may do in pursuit of the impartial good.…”
Section: Methodological Styles Of Ethical Theory and Impartialitymentioning
confidence: 99%
“…Psychological research has focused too much on the sacrificial dilemmas paradigm which essentially asks the negative question of how willing we are to kill others. However, recent research is starting to look at positive utilitarian demands (Kahane et al 2018;Jaquet and Cova 2021). As Mill pointed out, utilitarianism has a natural affinity with empathic concern for sentient beings.…”
mentioning
confidence: 99%
“…about the alleged toxicity of vaccines(Decety, Cowell, Lee et al (2015)). 28 Jaquet, Cova (2021).29 Adler (2017);Jaquet, Cova (2021);.…”
mentioning
confidence: 99%